2022
DOI: 10.3390/healthcare10112190
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Rationing of Nursing Care in Selected Polish Hospitals

Abstract: Introduction: The rationalization of nursing care can be a direct consequence of the low employment rate or unfavorable working environment of nurses. Aim: The aim of the study was to learn about the factors influencing the rationing of nursing care. Methods: The study group consisted of 209 nurses working in internal medicine departments. The study used the method of a diagnostic survey, a survey technique with the use of research tools: the BERNCA-R questionnaire and the PES-NWI questionnaire (which includes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
5
5
0
Order By: Relevance
“…In the Schubert et al study, the mean BERNCA score was 57 (1.69 ± 0.571) and, according to the authors, meant that nurses had to ration at least one of the 32 tasks indicated in the questionnaire during the last 7 days of work, which is confirmed by our own study and those of other authors ( 22 , 30 , 31 ). A slightly lower level of rationing (1.38 ± 0.62) was shown by Uchmanowicz et al study ( 32 ).…”
Section: Discussionsupporting
confidence: 79%
“…In the Schubert et al study, the mean BERNCA score was 57 (1.69 ± 0.571) and, according to the authors, meant that nurses had to ration at least one of the 32 tasks indicated in the questionnaire during the last 7 days of work, which is confirmed by our own study and those of other authors ( 22 , 30 , 31 ). A slightly lower level of rationing (1.38 ± 0.62) was shown by Uchmanowicz et al study ( 32 ).…”
Section: Discussionsupporting
confidence: 79%
“…The findings in this study align with results from other research. Radosz et al [ 26 ] confirmed the lack of influence of sociodemographic characteristics on the level of care rationing. Similarly, Wagner-Łosieczka et al [ 27 ] did not find a significant impact of sociodemographic characteristics of nursing staff on the level of nursing care rationing.…”
Section: Discussionmentioning
confidence: 99%
“…Radosz-Knawa et al covered 11 medical units and obtained an average care rationing score of 1.94 points, which means that care was also rarely rationed. However, the results of care rationing differed depending on the facility and ranged from 1.39 points (hospital 5) to 2.43 points (hospital 1), with the highest score being “sometimes” for rationing of care [ 16 ]. Rare rationing of care was also found among oncology nurses; the researchers obtained an average 1.55 points [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors explain the differences in the rationing of care between hospitals by the number of patients under the care of nurses, which was in the range of 13.11 (hospital 1)–6.31 (hospital 5) patients. They showed a correlation between the number of adverse events and the assessment of the work environment [ 16 ]. Cisek et al showed that there were 12–24 patients per nurse on duty [ 44 ], compared to 6–11 patients in the UK [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation